Benign Breast Disease Is Need Follow Up? - Hussein Sahan Jasim; Lateef Naif Razeek; Esam Abdalhameed Hasan (Zien Journals, 2022)
The vast majority of the lesions that occur in the breast are benign. Much concern is given to malignant lesions of the breast because breast cancer is the most common malignancy in women in Western countries; however, benign lesions of the breast are far more frequent than malignant ones .With the use of mammography, ultrasound, and magnetic resonance imaging of the breast and the extensive use of needle biopsies, the diagnosis of a benign breast disease can be accomplished without surgery in the majority of patients. Because the majority of benign lesions are not associated with an increased risk for subsequent breast cancer, unnecessary surgical procedures should be avoided The objective of this study is to: 1. Evaluate the benign breast disease in Balad city and its percentage. 2. Advice those women who need fallow up if there is risk of cancer
Keywords: Breast disease; benign breast disease; breast lesions and follow up